Study the effect of intention to use online social networks on brand performance with investigating the mediating role of customer-based brand equity - Davood Feiz; Mohsen Shafiee Nikabadi; fatemeh maleki (تحقیقات بازار یابی نوین, 2016)
Using online social networks and information collection from sites can affect purchasing behavior. Consumer cognize their friends' buying decisions more valuable to the anonymous' decisions and trust them more. This Study examine the impact of intention to use online social networks on brand's performance with emphasize on customer-based brand equity. Data were collected through a questionnaire that was distributed among 384 college students. Research findings suggest that there is a positive relationship between the intention to use online social networks and customer-based brand equity, but there is no significant relationship between the intention to use online social networks and Brand market performance. Also there is a positive relationship between customer-based brand equity and Brand market performance.